Familial Occurrence of Lymphocytic Colitis - Hugh J Freeman (Canadian Journal of Gastroenterology)
The familial occurrence of lymphocytic colitis in a female parent and her two female children is reported. No other genetically based disorder, including celiac disease, was evident. For both children, the age of diagnosis was more than two decades younger than the age of recognition of disease in the parent, and some clinical features, including the requirement for pharmacological agents in both children, suggested that their disease severity was more significant than that of the involved parent. These characteristics of a familial disease have been previously reported and labelled 'genetic anticipation' in some monogenetic forms of neurological disease, as well as in other types of inflammatory bowel diseases, including Crohn's disease. Alternatively, a common cohort effect related to a pathological environmental factor may have played a role in the pathogenesis of this disorder.